POSISI PEREMPUAN DALAM KONSEP DAN REALITAS: Kontroversi tentang Relasi Gender di Dunia Islam - Samsul Huda (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2020)
This article is to look for the meeting point of the debated term “qudrat” on the discourse of gender. The arising problems are stemming from the questions : is woman and man differ? and should one dominate others? These questions bring about controversion on woman position in Islam. The solutions suggested are to make the concept taken from the holy Quran be realized on all socio-cultural actuality into in all particularity of Islam. It is also a demand to undertake a sustainable effort to comprehend human development and their civilization and to actualize them with Islamic teachings, especially in gender relation problems.